Screening trials of spinal cord stimulation for neuropathic pain in England—A budget impact analysis - Duarte, Rui V.; Houten, Rachel; Nevitt, Sarah; Brookes, Morag; Bell, Jill; Earle, Jenny; Gulve, Ashish; Thomson, Simon; Baranidharan, Ganesan; North, Richard B.; Taylor, Rod S.; Eldabe, Sam (Frontiers in Pain Research, 2022)
Screening trials of spinal cord stimulation (SCS) prior to full implantation of a device are recommended by expert guidelines and international regulators. The current study sought to estimate the budget impact of a screening trial of SCS and the costs or savings of discontinuing the use of a screening trial. A budget impact analysis was performed considering a study population that reflects the size and characteristics of a patient population with neuropathic pain in England eligible for SCS. The perspective adopted was that of the NHS with a 5-year time horizon. The base case analysis indicate that a no screening trial strategy would result in cost-savings to the NHS England of £400,000–£500,000 per year. Sensitivity analyses were conducted to evaluate different scenarios. If ≥5% of the eligible neuropathic pain population received a SCS device, cost-savings would be >£2.5 million/year. In contrast, at the lowest assumed cost of a screening trial (£1,950/patient), a screening trial prior to SCS implantation would be cost-saving. The proportion of patients having an unsuccessful screening trial would have to be ≥14.4% for current practice of a screening trial to be cost-saving. The findings from this budget impact analysis support the results of a recent UK multicenter randomized controlled trial (TRIAL-STIM) of a policy for the discontinuation of compulsory SCS screening trials, namely that such a policy would result in considerable cost-savings to healthcare systems.